Antioxidant and α-glucosidase inhibitory activities of isolated compounds from ipomoea aquatica - Lawal, Umar; Shaari, Khozirah; Ismail, Intan Safinar; Khatib, Alfi; Abas, Faridah (ACG Publications, 2016)
Ipomoea aquatica Forsk is a green leafy vegetable that is a rich source of amino acids and vitamins. Antioxidant and α-glucosidase inhibitory activities of the hexane (IAHE) and methanol (IAME) fractions of the vegetable portion of I. aquatica were investigated. The IAME fraction exhibited a strong scavenging effect of the 2,2-diphenyl-2-picryl hydrazyl (DPPH) free radicals, and this fraction contained the highest phenolic contents. Phytochemical investigation of the IAME fraction yielded three known compounds, namely 3,5-di-O-caffeoylquinic acid (1), 4,5-di-O-caffeoylquinic acid (2) and quercetin 3-O-β-D-glucoside (3). The structures were unambiguously elucidated based on 1D and 2D-NMR analyses (1H, 13C, COSY, HSQC, HMBC) and mass spectrometry data. Compound 3 was isolated for the first time from this plant.